ISLAM AND GENDER JUSTICE - Nuril Farida Maratus (Universitas Islam Balitar, 2020)
The focus of this study is to discuss how Islamic perspectives are concerned with gender justice. This paper not only tries to provide philosophical and definitive arguments in response to anti-gender attitudes or parties who use the legitimacy of religious texts so as to justify gender as the nature in treating women, it also wants to provide understanding in measuring the nature of gender justice, so Islamic values continues to run on its dynamic nature in facing the challenges of the times. For this reason, adequate knowledge is needed about what is meant by “nature” and “gender”, so that it clearly finds differences between the two. The literature search results show that in essence the concept of gender justice can be determined by the community and its environment; it is dynamic and contextual, while “nature” is a fixed nature in someone given by God, such as the sex between men and women according to their respective functions.